Effect Of Green Human Resource Management, Green Marketing On Environmental Performance In Higher Education Institutions (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the relationship between Green Human Resource Management (GHRM), Green Marketing (GM) and Environmental Performance (EP) in Pakistan's Higher Education Institutions (HEIs). The researcher collected data from 251 employees working in different HEIs in Khyber Pakhtunkhwa, Pakistan and tested the hypotheses using Smaart Pls and JASP. GHRM and GM have a positive impact on Environmental performance. To maximize the benefits of GHRM practices, HEIs should adopt GHRM practices and GM strategies to enhance their environmental sustainability and increase their employees' ecological awareness. These results can inform the development of policies and procedures to promote ecological sustainability in HEIs in Pakistan and other similar contexts.